Effect of pH of Synthesis on CdS/L-cys Colloidal Solutions Optical Properties - Krupko, O.V.; Shcherbak, L.P.; Khalavka, Yu.B. (Physics and Chemistry of Solid State, 2016)
Using the measurements of absorption spectra and photoluminescence, as well as electron microscopic studies, the limits of concentrations of cadmium and sulfur ions and the stabilizer L-cysteine, suitable for obtaining stable colloidal solutions of quantum dots (size 1 - 5 nm) with CdS and high quantum yield. The influence of the initial pH values ​​of the reaction system within 7 - 11 on the absorption edge, photoluminescence and quantum yield of colloidal solutions of CdS / L-cis nanoparticles is shown. The results were systematized using the simplex lattice design of the Chefe method.